Potential of Miana Leaf Extract as Expectorant (Profile Place of Growing, Antioxidant, Sputum Contaminants, Antibacterial, MIC, MKC Expectorant) - Sesilia Rante Pakadang; Santi Sinala; Alfrida Monica Salasa; St Ratnah; Sisilia Teresia Rosmala Dewi; Maria Hilaria (Majalah Obat Tradisional, 2020)
Research has been conducted on the treatment of phlegm cough with miana leaf extract in vitro (effective dose of miana leaf extract as an expectorant and antibacterial agent causing cough with phlegm). The study aims to compare the antioxidant activity of miana leaves from 3 locations where it grows, determine the types of contaminant bacteria in the sputum of cough sufferers, determine the minimum value of inhibitor concentration (MIC) and MKC of miana leaves against the test bacteria causing cough with phlegm, determine the effective dose of miana leaves that can used as a reference for coughing up phlegm and proving the potential of miana leaves as a sputum thinner. Miana leaf extraction is done by the juicer method. Antioxidant activity testing uses the DPPH method. Determination of test bacteria is done by isolating and identifying contaminant bacteria in the sputum sample of cough with phlegm. Testing the effectiveness of miana leaves against test bacteria is determined by the liquid dilution method. Expectorant activity testing was determined by measuring the viscosity of mucus viscosity of cow intestine treated with miana leaf extract. The results found that antioxidant activity was influenced by the location where miana leaves grew with an antioxidant potential of IC72 0.072 mg/ml - 0.76 mg/ml. Contaminant bacteria from sputum samples of cough patients are Streptococcus pneumonia, Klebsiella pneumonia, Staphylococcus aureus, Staphylococcus epidermidis and Enterobacter agglomerans. MIC values for contaminant bacteria are 0.1% - 0.75% and MKC values are found between 0.25% - 1.75%. miana leaf extract has the potential as a sputum thinner at a concentration of 0.01% - 0.1%. The recommended dose of miana leaf extract as a cough with phlegm is 1.75% w/v.